2022
DOI: 10.2147/ppa.s355023
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Quality of Life in Southern Taiwan COPD Patients Using Long-Acting Bronchodilator

Abstract: Background To assess the health-related quality of life (HRQoL) of Taiwan patients with different stages of chronic obstructive pulmonary disease (COPD) and using different combination therapies and to explore the factors affecting HRQoL in these patients. Methods This cross-sectional study included outpatient participants aged 35 years old and older who were receiving long-acting bronchodilator treatment in one of two hospitals in Southern Taiwan. Participants were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Age is 65 years and above, and nonworking or retired; these demographic characteristics were similar to those of previous studies [21], [22]. Moreover, airflow obstruction severity for 79.5% of patients was categorized as GOLD 1 (mild) and GOLD 2 (moderate); this distribution is similar to that of COPD patients in other domestic and foreign studies [23], [24].…”
Section: Discussionsupporting
confidence: 85%
“…Age is 65 years and above, and nonworking or retired; these demographic characteristics were similar to those of previous studies [21], [22]. Moreover, airflow obstruction severity for 79.5% of patients was categorized as GOLD 1 (mild) and GOLD 2 (moderate); this distribution is similar to that of COPD patients in other domestic and foreign studies [23], [24].…”
Section: Discussionsupporting
confidence: 85%
“…For example, studies in South korea and Portugal have shown that the HRQoL was impaired in patients with COPD and other respiratory illnesses, and it further deteriorated with increase in disease severity. 29,31 The physical domain had the lowest perceived QoL. Several studies have also reported the physical environment among the domains with the lowest perceived QoL.…”
Section: Discussionmentioning
confidence: 96%